Deradicalization Of Religious Understanding Through The NU Online and Suara Muhammadiyah Website in The Perspective of Critical Discourse Analysis - Iswahyudi Iswahyudi; Udin Safala; Dwi Azizah Agustina (Dialogia, 2021)
This paper will discuss how two media (websites) NU Online and Suara Muhammadiyah counteract radicalism in terms of the Islamic state discourse. The post-reform discourse on the Islamic State is not only in seminar forums with a physical presence but has penetrated internet sites, Facebook, WA and others. The purpose of this paper is to answer three main problems, first, what are the radical aspects of the idea of an Islamic state published by the NU Online website and the Suara Muhammadiyah website? Second, how is the deradicalization of the NU Online website and the Suara Muhammadiyah website in terms of the Islamic state in Indonesia? and third, what is the ideology behind the NU Online website and the Suara Muhammadiyah website in deradicalizing the Islamic state in Indonesia? To answer these three main problems, this paper uses Norman Fairclough's critical discourse analysis approach. Fairclough was chosen because he has an in-depth study of language as a practice of power. Fairclough's critical discourse analysis focuses on the study of three interrelated things, namely text, discourse practice and sociocultural practice. This paper finds several things. First, the aspects of radicalism discussed by NU Online and Suara Muhammadiyah are on intolerance of the subject, An ahistorical concept and symbolic and physical violence. Second, the way of deradicalization of NU Online and Suara Muhammadiyah is through normative theological arguments, arguments on the historical practice of Islamic social politics and Indonesian factual conditions. Third, the ideology of NU Online is al-Sha>fi'i> with the development of an open Sufism epistemology and the Suara Muhammadiyah ideology which is the ideology of schools without madhhab in the form of progressive Islam.